Effect of Rock Phosphate on Nutrient Status and Nut Load of Mature Coconut in South-Western Ghana - Andoh-Mensah, E.; Addae-Manu, A.; Nutsukpo, D. K. (International Coconut Community, 2011)
The effect of rock phosphate on mature coconut was evaluated from 2004 to 2010 within the context of low nut yield due to phosphorus deficiency in the acidic soils of South-Western Ghana. A low reactive Togo rock phosphate containing 25.5% P205 was applied. Three application schedules based on 666 kg/ha rock phosphate and a control were evaluated in a Randomized Complete Block Design with five replications. The application schedules were: (a) Bulk application at 4.5 kg/tree (b) Two-equal-split application at 2.25 kg/tree in years 1and 3 (c) Three-equal-split application at 1.5 kg/ tree in years 1, 2 and 3. Muriate of potash fertilizer was applied at 2 kg/tree as basal treatment. Plot size was 0.2 ha comprising 30 trees. Nut load and leaf nutrient status of coconut palms were determined. Rock phosphate led to a significant (P<0.01) increase in leaf phosphorus and nut yield. It sustained a superior nut load for a 4-year period beginning from year 2 of application to year 5 with average nut gain of 19.0 per tree compared to 4.6 per tree in the control palms. There was no significant (P>0.05) difference in nut yield and nutrient status between bulk and split methods of rock phosphate application. A value-to-cost ratio of 1.5 was obtained thus indicating the profitability of rock phosphate application in the acidic soils of South-Western Ghana. Coir geotextiles find application in revegetation of slopes by stabilizing the soil through erosion control. It has been found that the longevity of coir geotextiles although highest among all the natural fibres, it is required to last for at least 5 years so as to sustain the vegetation on the slopes for a long term solution. Normally it is found that coir geotextiles lose their 50% strength in 6 months in contact with soil, therefore it is required to strengthen the coir geotextiles.